2008
DOI: 10.1021/jp711369e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Splitting of Titanate Fibers to Single-Crystalline TiO2 Nanostructures with Controllable Crystalline Phase, Morphology, Microstructure, and Photocatalytic Activity

Abstract: A simple and efficient inorganic acid-assisted hydrothermal route has been developed for the synthesis of single-crystalline TiO2nanostructures with use of protonic tetratitanate hydrate fibers as a precursor. A variety of TiO2 nanostructures, including aligned nanorods, nanoporous nanostructures, nanocubes, and diamond-shaped nanocrystals, have been prepared with this method. The morphology, crystalline phase, composition, average grain size, band gap, and microstructure of the nanostructures have been determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 60 publications
5
58
1
1
Order By: Relevance
“…Previous work also reveals that titanate nanowire will be fractionized into small single crystalline grains in more rigorous conditions [13]. Moreover, the growth mechanism of TiO 2 -B film has demonstrated that the (0k0) planes of TiO 2 -B were derived from the a-axis orientation of hydrogen titanate [14].…”
Section: Introductionmentioning
confidence: 98%
“…Previous work also reveals that titanate nanowire will be fractionized into small single crystalline grains in more rigorous conditions [13]. Moreover, the growth mechanism of TiO 2 -B film has demonstrated that the (0k0) planes of TiO 2 -B were derived from the a-axis orientation of hydrogen titanate [14].…”
Section: Introductionmentioning
confidence: 98%
“…A higher value of the constant k for a particular catalyst means that it has a higher activity for photodegradation of CR, which allows us to quantitatively determine the photocatalytic activities of the different catalysts [43]. The correlation constants for the fitted lines were calculated to be between 0.99 and 1, which indicates that the photocatalytic degradation of CR can be described by a first-order kinetic model.…”
Section: Degradation Of Cresol Redmentioning
confidence: 93%
“…It is shown that the photodegradation efficiency of the obtained TiO 2 could increase from 67.62% to 73.00% and 91.00% as R L/S decreased from 100:1 to 75:1 and 50:1, respectively, which may be ascribed to the different crystal phases and specific surface areas of as-synthesized TiO 2 . Larger specific surface area is beneficial to the adsorption of oxygen atoms to form active hydroxyl groups, resulting in enhancement of the photocatalytic activity (Shen et al, 2008). As shown in Fig.…”
Section: Mechanism Of Crystalline Phase Transformation and Morphologymentioning
confidence: 98%
“…However, the photocatalytic performance would be improved greatly if the crystalline phase and morphology of the prepared TiO 2 photocatalyst could be controlled, since the properties of TiO 2 photocatalysts are closely related to its crystalline phase and morphology. Up to now, a variety of TiO 2 photocatalysts with different crystalline phases and morphologies have only been synthesized from chemical reagents (Li et al, 2006(Li et al, , 2008Shen et al, 2008;Sun et al, 2011;Zhou et al, 2011). Therefore, synthesis of a TiO 2 photocatalyst with controlled crystalline phase and morphology from Ti-bearing EAF slag under mild treatment conditions will be the focus of this study.…”
Section: Introductionmentioning
confidence: 99%